Cultural Perceptions : Latvian Exchange Program - Konsella, Rachel J.; Roffers, Kimberly Jean; Ekenstedt, Megan; Gantert, Lydia; Terpstra, Glenn Allen (My University, 2011)
The objective of this research was to stretch scholarly and professional boundaries of perception, photographic vision, and personal understanding within an international collaborative environment between faculty and students. In sharing nad interpreting aural and visual culture between the University of Wisconsin--Eau Claire and The Latvian Culture College in Riga, Latvia, the objective was realized through successful research presentations and exhibitions.
Color poster with text, images, and photographs.
Keywords: Photography--Exhibitions; Latvia--Social life and customs; Posters; Cross-cultural perspectives; University of Wisconsin--Eau Claire. Latvian Exchange Program